2021
DOI: 10.1108/jes-06-2021-0273
|View full text |Cite
|
Sign up to set email alerts
|

A non-parametric framework for evaluating governance–efficiency–productivity associations in commercial banking

Abstract: PurposeAgainst the backdrop of an Indian banking sector that finds itself entangled in the triple deadlock of increasing competition, technological changes and strict regulatory compliance, the study aims to examine the need for reinforcing stringent corporate and risk governance mechanisms as an instrument for improving efficiency and productivity levels.Design/methodology/approachThe authors construct three separate indices, namely, supervisory board index, audit index and risk governance index to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Further, we explore the impact of external audit quality on NPLs. We find that external audit quality (AQ) has significant negative impact on the NPLs (see also Chowdhury 2012;Prakash et al 2021). It reveals that quality audit can reduce NPLs, identified as white collar crime in banking industry of Bangladesh (see also Ghosh et al 2020).…”
Section: Regression Results and Interpretationmentioning
confidence: 79%
See 4 more Smart Citations
“…Further, we explore the impact of external audit quality on NPLs. We find that external audit quality (AQ) has significant negative impact on the NPLs (see also Chowdhury 2012;Prakash et al 2021). It reveals that quality audit can reduce NPLs, identified as white collar crime in banking industry of Bangladesh (see also Ghosh et al 2020).…”
Section: Regression Results and Interpretationmentioning
confidence: 79%
“…AUDIT COMMITTEE INDEPENDENCE AND NPLs Ghosh et al (2020) identified that the lack of proper monitoring and nepotism have significant positive impact on NPLs in Bangladesh. Evaluating relationship between governance and efficiency, Prakash et al (2021) found that strong risk governance frameworks impede the adverse consequences of high regulatory capital and expand efficiency. Next, Fiador and Sarpong-Kumankoma (2021) found that a large board comprising experts and non-executive members can contribute to the bank loan quality.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations